2017
DOI: 10.1371/journal.pone.0178909
|View full text |Cite
|
Sign up to set email alerts
|

Genotype diversity and molecular evolution of noroviruses: A 30-year (1982-2011) comprehensive study with children from Northern Brazil

Abstract: A chronologically comprehensive 30-year study was conducted that involved children living in Belém, in the Amazon region of Northern Brazil, who participated in eight different studies from October 1982 to April 2011. The children were followed either in the community or in health units and hospitals in order to identify the norovirus genotypes involved in infections during this time. A total of 2,520 fecal specimens were obtained and subjected to RT-PCR and nucleotide sequencing for regions A, B, C, D and P2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 70 publications
(80 reference statements)
2
11
0
4
Order By: Relevance
“…(iii) GII.1 capsid genotype found in this study has been recently reported in Cameroon [48], Brazil [49,50], Australia [51], India [52], and elsewhere [53][54][55]. is genotype is frequently reported from both clinical cases and environmental samples.…”
Section: Discussionsupporting
confidence: 74%
“…(iii) GII.1 capsid genotype found in this study has been recently reported in Cameroon [48], Brazil [49,50], Australia [51], India [52], and elsewhere [53][54][55]. is genotype is frequently reported from both clinical cases and environmental samples.…”
Section: Discussionsupporting
confidence: 74%
“…The relaxed-clock estimations calculated similar rates of evolution in Manaus (Sydney: 7.7 × 10 − 3 ; New Orleans: 6.3 × 10 − 3 ) to other studies, which reported 6.99 × 10 − 3 and 7.3 × 10 − 3 subst./site/year for full VP1 and subdomain P2 gene sequences, respectively [ 48 , 49 ]. In a study conducted in Belem, a state adjacent to Manaus, over 30 years, Siqueira et al [ 50 ] found an evolutionary rate of 9.05 × 10 − 3 subs./site/year for other GII.4 variants. The time-scale evolutional was constructed based on the subdomain P2, which is the most hypervariable region in VP1, which are under selection pressure of the immunological system.…”
Section: Discussionmentioning
confidence: 99%
“…This methodology has already been used in other studies, carried out in the Amazon region, establishing higher positive rates [ 44 , 52 , 53 ]. Uncommon recombinants strains (GII.P21/GII.2, GII.13/GII.17, GII.P21/GII.3) and emergent variants (GII.4_Sydney) were also detected by EIA [ 50 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conformational epitope analyses using in silico approaches also enable us to identify and map binding sites of host antibodies on three-dimensional structures of proteins (Potocnakova et al, 2016 ). For HuNoV, a large number of studies on viral evolution have been performed using bioinformatics (Giammanco et al, 2014 ; Kimura et al, 2015 ; Kobayashi et al, 2015 , 2016 ; Lu et al, 2016 ; Parra et al, 2017 ; Siqueira et al, 2017 ; Tohma et al, 2017 ). Previous reports described the evolutionary rates of some HuNoV genotypes using the Bayesian MCMC method and linear regression analyses, which suggested differences in such rates among the genotypes (Parra et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%